2004
DOI: 10.1158/0008-5472.can-04-0138
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Dendritic Cells with Antigen-Containing Liposomes

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
74
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 239 publications
(78 citation statements)
references
References 44 publications
1
74
0
Order By: Relevance
“…High-level expression of CD11c by DC renders it an attractive antigen target for vaccination purposes. Indeed, a previous study reported modifying liposomes with Fab fragments of the anti-CD11c antibody to specifically target DC [22], while others have shown enhancement of antibody responses [23] by targeting DC through CD11c. Castro et al [19] demonstrate that CD11c-targeting is also capable of facilitating strong CTL generation.…”
mentioning
confidence: 99%
“…High-level expression of CD11c by DC renders it an attractive antigen target for vaccination purposes. Indeed, a previous study reported modifying liposomes with Fab fragments of the anti-CD11c antibody to specifically target DC [22], while others have shown enhancement of antibody responses [23] by targeting DC through CD11c. Castro et al [19] demonstrate that CD11c-targeting is also capable of facilitating strong CTL generation.…”
mentioning
confidence: 99%
“…This is a complicated and expensive process. 529 However, several recent studies used antibodies, antibody fragments, or other ligands that bind to dendritic cells to specifically deliver antigens in vivo. 529–534 Accordingly, peptides can be used to specifically target antigens in vivo.…”
Section: Use Of Peptides For Therapymentioning
confidence: 99%
“…DEC-205 was also exploited as an internalization receptor for bispecific mAbs [111], the second paratope of which was against biotin, allowing the authors to couple biotinylated OVA as a model antigen. van Broekhoven et al [112] coupled an anti-DEC-205 mAb to the surface of plasma membrane vesicles prepared from the B16-OVA mouse melanoma or the surface of OVA-containing liposomes. Both these preparations targeted DCs and stimulated anti-OVA CTL responses and tumor protection in immunized mice.…”
Section: Targeting Antigens To DC Surface Receptorsmentioning
confidence: 99%